Publicações nacionais sobre CALL e outras tecnologias no ensino e aprendizagem de línguas estrangeiras : um olhar na segunda década do século XXI - Guedes, Roberta de Oliveira (2015)
Among the various human activities, it is possible to observe the presence and the use of technologies in different situations of daily life, such as at work, in schools, at family times and leisure (SANTOS, 2013, MIRANDA, 2013, REIS, 2010). However, there is a shortage of research on CALL (Computer Assisted Language Learning), technology and teaching and learning of Foreign Languages (REIS, 2010). Based on this scenario and on government initiatives, institutions such as UNESCO and universities that develop research on technology in several areas, we propose the development of this work that aims to discuss the publications in national academic journals, classified with QUALIS A (AI and A2) in Language/ Linguistics area. Our analysis comprehends the years 2010-2014. These publications are evaluated by the Coordination for the Improvement of Higher Education Personnel (CAPES), recognized as a reliable reference by the researchers in identifying national journals (BONINI, 2004). It is, therefore, a study that selects research papers from specific journals as the particular objects being examined, characterizing an instrumental case study, as proposed Stake (1994). From these publications, we analyze the concepts of language, technology, and possible methodologies used, encompassing also the results, limitations and some of the referrals found in order to understand at what stage the research nationally published in the area is. Through data collection and analysis, we identified those publications that have online digital editions of free access and at the same time bring teaching subjects and foreign language learning, CALL and technology as theme in their published papers. Based on the results, we have noticed the incipience of studies in the area, according to the literature in our field of research. Besides, we could verify the presence of various objects that compose the covered studies, the different impacts of technology in language teaching (LT), the need of technological knowledge by the teachers, factors that may be addressed in other investigations, once we experience a national context that seems to require more academic disclosure about this theme.